GeoSDH @ GEOWEB 4.0 - Vi spieghiamo il futuro di GEOWEB: servizi innovativi basati su informazioni geospaziali - GEOWEB, Team di sviluppo (GEOmedia, 2018)
Innovation runs fast on the edge of the cloud computer science and GEOWEB, company born in the 2000s following the digital cadastre and telematics services for surveyors, industrial surveyors, agricultural surveyors, adapt its services to the needs of professionals. Infact GEOWEB proposes in this article all its new cloud based GeoSDH services: GeoDaC (Geospatial Data Cloud) - DecoSEL (Selective Deconstruction) - 3DCapture and Project Management Unit Service.